Holomorphic families of immersions and higher analytic torsion forms - Bismut Jean-Michel (Paris Societe Mathematique de France, 1997)
The purpose of this paper is to calculate the behaviour of the higher analytic torsion forms of a K
Keywords: Differential geometry; Kahler fibration; Torsion